BINUS Online Learning Web User Experience Improvement - Lena Chow (Engineering, MAthematics and Computer Science (EMACS) Journal, 2020)
With the technology nowadays where information is one click away, news travels within seconds through online news, social media, chat, etc. It’s not impossible anymore for someone who lived miles away to get information at the same time with someone who live near the news’ source.  New business starts to grow aligned with advancement in information technologies to tap bigger market. Each of them have different ways of showcasing their products, and how they showcase products can influence their customers to continue using it and to eventually make decision to purchase. Stores are available in e-market form, public transportations’ tickets are available online, education industries start to have websites, some of them even have online classes. Whether you are a busy professional looking for the next career step or a school leaver wanting to start your career without sacrificing your education, online study would be the solution. Committed to providing a world class education with international learning experience that makes positive contributions to the global community, BINUS University implemented a method called BINUS Online Learning. The method allows students not to come to campus, because almost all lectures conducted through the online system. Learning-teaching activities are in BINUS Online Learning web (Learning Management System). To ensure Binus online web can be used as tool to achieve Binus online mission, then improvement should be done continuously. This paper will search for continuous improvement especially user experience.